Lipoapoptosis Pathways in Pancreatic β-Cells and the Anti-Apoptosis Mechanisms of Adiponectin - Long, J.; Su, Y. X.; Deng, H. C. (Hormone and Metabolic Research, 2014)
Lipoapoptosis is the main form of pancreatic β-cell death in diabetes. Adiponectin is an adipocyte-derived hormone, which has anti-apoptosis effect in numerous cells. The present study was designed to explore the role of the ‘extrinsic’ (death receptor-induced) and the ‘intrinsic’ (mitochondrial) pathways in pancreatic β-cell lipoapoptosis and the anti-apoptosis effect of adiponectin on pancreatic β-cells. Palmitate (0.4 mmol/l) or oleate (0.4 mmol/l) was used to induce the apoptosis of Min 6 cells for 24 h. Z-LETD-FMK or Z-IEHD-FMK (40 μM) was used to inhibit the activity of caspase-8 or -9. When adiponectin was used, Min 6 cultures were pretreated in the absence or presence of fAd (5 μg/ml) for 2 h and then subjected to palmitate for 24 h. Apoptosis was evaluated using Annexin V-Cy3 kit. The expression levels of cleaved caspase-3, -8, -9, B-cell lymphoma 2 (BCL-2), and Bax were examined by Western blotting. Palmitate-induced pancreatic β-cell apoptosis was accompanied by the activation of caspase-8, -9, and -3. Blockade of casapse-9 rather than caspase-8, showed an inhibitory effect on caspase-3 activation. Moreover, adiponectin treatment prevented palmitate-induced apoptosis by inhibition of caspase-9 activation, but not of caspase-8, and induced an upregulation of BCL-2 and a downregulation of Bax in protein level. Both extrinsic and intrinsic pathways are activated in pancreatic β-cell lipoapoptosis, and the intrinsic apoptosis pathway is the major one. Adiponectin prevents pancreatic β-cells from apoptosis by inhibition of intrinsic apoptosis pathway via regulation of the BCL2 family. Therefore, protection of intrinsic apoptosis pathway is a potential therapeutic strategy for diabetes.
Keywords: lipoapoptosis; adiponectin; extrinsic pathway; intrinsic pathway